The direct and mediating effect of social support on health-related quality of life during pregnancy among Australian women - Asres Bedaso; Jon Adams; Wenbo Peng; David Sibbritt (BMC, 2023)
Abstract Background Prenatal stress can have a negative effect on the quality of life (QoL) of pregnant women. Social support plays a vital role in improving the psychological well-being of pregnant women by enhancing their stress-coping ability. The current study assessed the association between social support and health-related quality of life (HRQoL) as well as the mediating role of social support in the linkage between perceived stress and HRQoL among pregnant Australian women. Methods Secondary data was obtained from 493 women who reported being pregnant in survey six of the 1973-78 cohort of the Australian Longitudinal Study on Women's Health (ALSWH). Social support and perceived stress were assessed using the Medical Outcomes Study Social Support Index (MOS-SSS-19) and the Perceived Stress Scale, respectively. The Mental Component Scale (MCS) and Physical Component Scale (PCS) of the SF-36 were used to examine the mental and physical HRQoL. A mediation model was used to examine the mediating effect of social support in the relationship between perceived stress and HRQoL. A multivariate quantile regression (QR) model was used to assess the association between social support and HRQoL after adjusting for potential confounders. Result The mean age of the pregnant women was 35.8 years. The mediational analysis revealed that emotional/informational support (β= -1.53; 95% CI: -2.36, -0.78), tangible support (β= -0.64; 95% CI: -1.29, -0.09), and affectionate support/positive social interaction (β= -1.33; 95% CI: -2.25, -0.48), played a significant mediating role in the relationship between perceived stress and mental health-related QoL. In addition, perceived stress had a significant indirect effect on mental health-related QoL through overall social support (β = -1.38; 95% CI: -2.28, -0.56), and the mediator accounted for approximately 14.3% of the total effect. The multivariate QR analysis indicated that all the domains of social support and overall social support scores were positively associated with higher MCS scores (p < 0.05). However, social support was found to have no significant association with PCS (p > 0.05). Conclusion Social support plays a direct and mediating role in improving the HRQoL of pregnant Australian women. Maternal health professionals need to consider social support as an essential tool to improve the HRQoL of pregnant women. Further, as part of routine antenatal care activity, assessing pregnant women's level of social support is beneficial.